Integrated waqf based islamic microfinance model (IWIMM) for poverty alleviation in OIC member countries - Haneef, Mohamed Aslam; Pramanik, Ataul Huq; Mohammed, Mustafa Omar; Muhammad, Aliyu Dahiru (IDOSI Publications, 2014)
Poverty dominates the agenda of developing countries. Poverty was and still is one of the major impediments of human progress and societal development. Its existence is as old as human history while its alleviation is attributed to effective and successfull economic policies. Various approaches/policies are offered towards reducing poverty. These policies vary depending on time, space and the country concernced. However, reduction of poverty the major goal of many economic systems as stated by the Millenium Development Goals, thought sometimes not explicitly stated It was found that in OIC member countries religious and cultural norms drive preference of Islamic microfinance over conventional microfinance.The study further developed an Integrated waqf based Islamic micrfinance model (IWIMM) for poverty reduction in OIC memebr countries.This is expected to overcome the challenges of conventional microfinance such as, high cost of capital, low quality of human resource, vulnerabilites of poor borrowers due to lack of sustainable takaful and limited products for the clients with different occupationanl backgrounds. However, the model is yet to be verified empirically. Thus, further studies should be conducted to test the model using quantitative techniques such as, structural equation modelling (SEM).